Pengaruh Pemberian Ransum Yang Mengandung Tepung Kulit Buah Pepaya (Carica papaya) Terhadap Produksi dan Komponen Karkas Kelinci Peranakan New Zealand White Jantan - Sauland Sinaga; Marsudin Silalahi; Rikas P (Politeknik Negeri Lampung., 2012)
The experiment studied The Effect of papaya rind meal in Carcass production dan Component of the New Zealand white Male Rabbit Cross. It was conducted from 14th July to 7th September 2008 at Panorama Jatinangor, Sumedang. The objective of this experiment was to find out the Effect of papaya rind meal in Carcas production dan Component of the New Zealand white Male Rabbit Cross. This experimentally method was done on 20 New Zealand White rabbits cross. The experimental design used Completely Random Design (CRD) with four threatments of (R0= without papaya rind meal, R1= 5, R2= 10, and R3= 15 percent for papaya rind meal), each threatments had five replications. Data collected were tested statistically by variance method. According to the experiment result, it is showed that papaya rind meal within ration up to 15% in feeding gave non significant result on carcass weight (712,40 gram,±64,06), meat percentage (58,53%±5,88), bone percentage (34,66% ±0,59) and fat percentage (10,31%±0,87) of rabbit and it can be used as an alternative protein source of feed stuff without had negative effect to carcass production and component. Keywords : Papaya Rind Meal, Rabbit, Carcass Production and Component.